The Detail Engineering Design (DED) Online Garbage Collection System - Verlin, Lino; Wirastuti, NMAE Dewi (Journal of Electrical, Electronics and Informatics; Vol 7 No 1 (2023): JEEI (July 2023), 2023)
Garbage is an invaluable or worthless object that is around the community environment. Almost all cities in Indonesia experience problems in waste management. This happens because the Final Disposal Site in a city does not have enough land to accommodate. The lack of landfills has resulted in people throwing garbage into ditches, rivers and the sea. Community participation is another important factor in waste management but also necessary to utilize modern technology. Therefore to overcome to overcome this waste problem by creating an Detail Engineering Design for online Garbage Collection System. This system developed to help the process of sending waste from households to TPS and sending garbage from TPS to TPA. The results of this study are detailed engineering systems for online garbage collection which are expected to help local governments in overcoming problems with garbage. With the example of the implementation of this system for Tabanan district. The estimated funds needed are Rp. 20,607,450,400. These funds are used to build a garbage collection site or landfill and develop the application and the time required for the overall construction is six months